Political and institutional drivers of social security universalization in Brazil - Marcus André Campelo de Melo (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper discusses the political and institutional factors that shaped the emergence and consolidation of a universal health system (SUS) in Brazil after the transition to democracy in the late 1980s. It argues that a combination of political incentives and political, fiscal and institutional capacities have been at the root of the process of creating such a system. First, the political incentives have been associated with a competitive political system leading a race to serve poor constituencies and to the policy communities and activists within and outside the state. SUS benefitted from this political dynamic and thus became politically sustainable. Second, fiscal capacity and sustainability have been secured by a massive increased taxation and earmarked social expenditures. Third, the systems success stems from the institutional capacity to run a complex decentralized system. The system appears to reach its limit in terms of the capacity to extend coverage in a context where there is universal formal entitlement to health, but some 30 per cent of the population has access to private insurance. Despite many improvements, many challenges continue to beset the delivery of health care in Brazil, and addressing them adequately will require significant policy changes, not only additional resources. However, finding resources has proven increasingly costly politically and improvements will have to be achieved through efficiency gains. Politically, this is a situation of a zero sum game rather than that of the positive game typical of coverage expansion. Most importantly, the perceived increased personal risks are leading citizens to support creating new resources for the system and for policies to improve the quality of care. A new window of opportunity thus seems to have been opened.
Keywords: 330